Acute cyclosporine overdose in a child with nephrotic syndrome: a case report and literature review - Song, Eun Song; Yang, Eun Mi (Frontiers in Pediatrics, 2026)
BackgroundCalcineurin inhibitors are widely used in organ transplantation and nephrotic syndrome, with chronic toxicities well documented, but acute toxicity is rarely reported.Case presentationWe report a 3.9-year-old boy with steroid-dependent nephrotic syndrome who accidentally ingested a single dose of cyclosporine A (CsA) at 75 mg/kg (1,500 mg)— over 20 times the intended dose of 3.5 mg/kg (70 mg)—due to medication error. He developed transient abdominal pain, diarrhea, and vomiting, which resolved without treatment. Error was discovered 12 h post-ingestion, and he was hospitalized with a CsA trough level of 1003 ng/mL (measured 13 h after ingestion), yet remained clinically stable. Management included CsA discontinuation, intravenous hydration, rifampin- and phenobarbital-induced cytochrome P450 activation, resulting in normalization of CsA levels within 48 h. A literature review identified 28 pediatric cases of acute CsA overdose, with presentations ranging from asymptomatic to severe neurotoxicity and acute kidney injury. The varied, including supportive care, gastrointestinal decontamination, and enzyme induction, with generally favorable outcomes.ConclusionsAlthough rare, acute CsA overdose in children can pose serious risks. This case and review underscore the symptoms of overdose and prompt intervention to prevent complications.